Growth, development and content of flavonoids in calendula (Calendula officinalis L.) - Isabela Cristina Gomes Honório; Filipe Pereira Giardini Bonfim; Sebastián Giraldo Montoya; Vicente Vagner Dias Casali; João Paulo Viana Leite; Paulo Roberto Cecon (Acta Scientiarum: Agronomy, 2016)
Flavonoids, the pharmaco-active compounds studied in this work, in general, are located in the shoots as natural pigments that protect the plants from damage by oxidizing agents. The experiment was conducted in the greenhouse of the Fitotecnia Department, Federal University of Viçosa, Minas Gerais Staty. The experimental design was completely randomized with five treatments and five replications. The treatments were the time of harvest: zero, three, six, nine, and twelve days after anthesis (DAA). The height of the plant (mm), stem diameter (mm), number of leaves and total flavonoid content (%, w w-1) were determined. We developed growth curves for calendula with growth behavior assessed through time for height, stem diameter and number of leaves. The time of the harvest season positively influenced the total flavonoid contents and the average productivity of flowers, and the highest content of flavonoids was found three DAA. The average productivity of the flowers and the accumulation of flavonoids were heterogeneous among harvest times (0, 3, 6, 9 and 12 days after anthesis). The highest yield of flavonoids was obtained three days after anthesis; therefore, a harvest of the inflorescences is recommended every three days.